2013
DOI: 10.1016/j.ijepes.2012.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Electrical earthing in troubled environment

Abstract: Practical challenges of electrical earthing in both steady and transient states have been revisited. By analyzing the cases based on theoretical and practical aspects, engineering guidelines are proposed to develop suitable solutions. Less complicated cases can be approached with various electrode configurations such as multiple ring, antenna, crow-foot and centipede arrangements. Distributed earthing arrangements treated with backfill materials are suitable for the sites with extremely high resistive soil. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Very high values of the EPR have been found that request the realization of specific measures [16,17] for the reduction of the dangerous touch and step voltages.…”
Section: Resultsmentioning
confidence: 99%
“…Very high values of the EPR have been found that request the realization of specific measures [16,17] for the reduction of the dangerous touch and step voltages.…”
Section: Resultsmentioning
confidence: 99%
“…Earth electrodes are permitted to be installed inside the structure through the basement, or by using natural elements inside the structure as the ring conductors for the type B earthing systems as well [3]. However there are several criteria to be satisfied for such usage [2].Earthing under pathological soil conditions has been addressed in [4][5][6] B…”
Section: Lightning Protection Systemsmentioning
confidence: 99%
“…It is recommended for services to enter the LPZ at one location and connect to bonding bar at one point, if it is not possible there should be different bonding bars which finally interconnected together. Moreover, by shielding of internal lines, the mutual induction effect would be minimized, also routing electrical and signal lines together will minimize the induction loop and passing them close to the natural components of the structure that is earthed as well [4][5][6][7], [5][6][7][8].…”
Section: Internal Lpsmentioning
confidence: 99%
“…The electrical resistivity of geo-materials has attracted the attention of the researchers since 1912 when Schlumberger used the electrical resistivity measurements to characterize the subsurface ground (Griffiths & King, 1965). Since then, the need to understand the behavior of electrical resistivity of soils has been extended to different areas such as design of electrical earthing system, monitoring moisture content for agriculture applications, electro-osmosis consolidation and drainage of soils, and assessing the homogeneity of compacted clay liner (Laver & Griffiths, 2001;Lim et al, 2013;Rhoades et al, 1976;Abu-Hassanein et al, 1996;Tabbagh et al, 2002;Brillante et al, 2015;Jones et al, 2011;Al Rashid et al, 2018).…”
Section: Introductionmentioning
confidence: 99%